The Role of Transformational Leadership in Developing Employability Skills Among Vocational High School Students: A Career Guidance Perspective - Novia Nailatun Nufus; Tuwoso; Hary Suswanto (Indonesian Scientific Publication, 2026)
This study aims to examine the role of transformational leadership in developing employability skills among vocational high school students from the perspective of career guidance. A Systematic Literature Review (SLR) approach following the PRISMA framework was employed to synthesize previous studies related to transformational leadership, employability skills, vocational education, and career guidance. Literature data were collected from Google Scholar, Scopus Preview, ERIC, and DOAJ databases. A total of 89 articles were initially identified, and 23 peer-reviewed studies published between 2020 and 2026 met the inclusion criteria for final analysis. Thematic synthesis was used to identify major themes related to educational leadership, employability development, workforce readiness, and career adaptability. The findings indicate that transformational leadership contributes to supportive learning environments that encourage motivation, collaboration, adaptability, creativity, and professional confidence among vocational students. Career guidance was also found to support career planning, career adaptability, and workforce readiness. However, most reviewed studies focused on general vocational education contexts, while evidence specifically related to Fashion Design vocational students remains limited. This study contributes conceptually by integrating transformational leadership, employability skills, and career guidance perspectives within vocational education. The findings provide practical implications for school leaders, teachers, and career counselors in strengthening employability-oriented learning environments.